Close neighbours matter: neighbourhood effects on early performance at school - Dominique Goux; Eric Maurin (Institute for the Study of Labor (IZA), 2006)
Children's outcomes are strongly correlated with those of their neighbours. The extent to which this is causal is the subject of an extensive literature. An identification problem exists because people with similar characteristics are observed to live in close proximity. Another major difficulty is that neighbourhoods measured in available data are often considerably larger than those which matter for outcomes (i.e. close neighbours). Several institutional features of France enable us to address these problems. We find that an adolescent's performance at the end of junior high-school are strongly influenced by the performance of other adolescents in the neighbourhood.
Keywords: I21; J24; 330; neighborhood effects on education; Schüler; Jugendliche; Lernen; Motivation; Bildungsniveau; Frankreich; Soziale Beziehungen